Clinical and Financial Implications of Medicine Consumption Patterns at a Leading Referral Hospital in Kenya to Guide Future Planning of Care - Kivoto, Patrick M.; Mulaku, Mercy; Ouma, Charles; Ferrario, Alessandra; Kurdi, Amanj; Godman, Brian; Oluka, Margaret (Frontiers in Pharmacology, 2018)
Background: Medicines can constitute up to 70% of total health care budgets in developing countries as well as considerable expenditure in hospitals. Inventory management techniques can assist with managing resources efficiently. In Kenyatta National Hospital (KNH), a leading hospital in Kenya, over 30% of medical expenses are currently allocated to medicines, and this needs to be optimally managed. Objective: To investigate drug consumption patterns, their costs and morbidity patterns at KNH in recent year. Methodology: Cross-sectional retrospective record review. Inventory control techniques, ABC (Always, Better, Control), VEN (Vital, Essential and Non-essential) and ABC-VEN matrix analysis used to study drug expenditure patterns. Morbidity data extracted from the Medical Records. Results: Out of an average of 811 medicine types procured annually (ATC 5), 80% were formulary drugs and 20% were non-formulary. Class A medicines constituted 13.2% to 14.2% of different medicines procured each year but accounted for an average of 80% of total annual drug expenditure. Class B medicines constituted 15.9%-17% of all the drugs procured yearly but accounted for 15% of the annual expenditure, whilst Class C medicines constituted 70% of total medicines procured but only 5% of the total expenditure. Vital and Essential medicines consumed the highest percentage of drug expenditure. ABC-VEN categorization showed that an average of 31% medicine types consumed an average of 85% of total drug expenditure. Therapeutic category and Morbidity patterns analysis showed a mismatch between drug expenditure and morbidity patterns in over 85% of the categories. Conclusion: Class A medicines are few but consume the largest proportion of hospital drug expenditure. Vital and essential items consume the highest drug expenditure, and need to be carefully managed. ABC-VEN categorization identified medicines were major savings could potentially be made helped by Therapeutic category and Morbidity pattern analysis. There was a high percentage of non-formulary items, which needs to be addressed. Inventory control techniques should be applied routinely to optimize medicine use within available budgets especially in low and middle income countries. This is now being implemented.